PENGARUH MEDIA TANAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN BIBIT BAKAU MINYAK (Rhizophora apiculata) - Gamelasari, Evi; Asfaruddin, Asfaruddin; Prihanani, Prihanani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This study aims to determine the effect of planting media on the growth of Oil Mangrove (Rhizophora apicutala) seedlings, to determine the effect of NPK fertilizer doses on Oil Mangrove (Rhizophora apicutala) seedling growth, to determine the interaction effect of planting media and NPK fertilizer doses on Oil Mangrove seedling growth. (Rhizophora apicutala). This study used a factorial randomized block design, with the first factor being the planting medium (M) consisting of M1: Topsoil, M2: Sandy Mud Soil, and the second factor being the dose of NPK fertilizer (B) consisting of B1: 0 g/polybag, B2: 9 g/polybag, B3: 12 g/polybag, B4: 15 g/polybag. The treatment was repeated 3 times to obtain 24 experimental units. The research showed that the treatment of planting media had no significant effect on the growth of oil mangrove seedlings (Rhizophora apiculata) except for the seedling height of 4 WAP, the NPK dose treatment had a significant effect on the growth of oil mangrove seedlings except for the variable number of leaves 4 WAP, 8 WAP, and dry weight, treatment interactions. the planting medium and doses of NPK fertilizer had no significant effect on the growth of oil mangrove seedlings (Rhizophora apiculata) except for plant height of 4 WAP, the dose of NPK 15 g/polybag gave the best growth of oil mangrove seedlings.